The Analysis of Anecdotes of Nasreddin Hodja in The Context of the Concepts Crime and Punishment - Senocak, Ebru; Ozmen, Ferhat (Geleneksel Yayincilik Ltd Stl, 2022)
The concepts crime and punishment are mentioned together with human history, and constitute the basis of criminal law. Crime, which is defined as a punished act, is related to behaviors that are against customs, moral and laws. The individual who causes chaos is penalized with the criminal law that foresees the abolishing of acts that damage the society, and the society order and security are ensured again. Literate types are fictious works that bear the traces of life. The subject of crime and punishment, which is considered within the types based on narration, invite the individual towards harmony with various examples full of sanctions, giving concrete information on behaviors that act in violation of social order and their punishments. The crime and punishment phenomena are mentioned through humor in anecdotes described around a type. Anecdots are full of lived phenomenon that carry the traces of real life. Being a type that is concise yet full of intense narration, anecdotes criticize the individual and thus act as a mirror that enables the reader to see himselfiherself. Anecdote types take a role at the main center, serving to the purpose of pronouncing and criticizing the problems of the society, generating solutions and taking the reader towards realization with ironical messages. Anecdotes are also a place of cultural memory. Nasreddin Hodja, who was a strong spokesman with multiple personality for the social subconscious identifying with the social realities of Turkish society, was often the guardian of public order and the enforcer of the law in his anecdotes. Nasreddin Hodja criticizes/punishes any actions that disturb the community without hesitating through the perspective of humor. Among those he punished, there are judges, statesmen, thieves, rulers as well as donkeys/oxen. In the background of punitive events seen in Nasreddin Hodja's anecdotes such as bribery and theft, there are traces of historical and socio-cultural life of the century when Nasreddin Hodja lived/was cherished. The negative effects of historical and social events on the public such as the Crusades of the 13th century, the defeat in the KOsedag War in 1243, the pressure of Mongols, the disorder of the state governance, etc. were also reflected in the anecdotes. The greatest basis that Anatolian people stood on in this dark age full of depressions were the wisdom-filled words of Hz. Mevlana and Yunus Emre and the anecdotes of Nasreddin Hodja that make you think and educate while making you laugh. The aforementioned scholars aimed to reach the people with the power of love, tolerance and belief and to give them tenacity, joy of life and the power to stand, and they endeavored to reintegrate the individual, who made a mistake, into society by ending the crimes committed. The examples of crimes and punishments identified in Nasreddin Hodja's anecdotes are the reflections of the century in which he lived / was cherished, and show the similarity of written law and oral law. Punishment in the anecdotes of Nasreddin Hodja have been imposed on directing/changing the behaviors of individuals, establishing the delayed justice, maintaining social order, ensuring social control, etc. The individuals with opposing values have been criticized with the aforementioned punishments, and the malevolent types who broke the moral rules, disrupted the integrity of the society and gave false testimony have been punished and legal awareness has been created. While the diversity of crimes and punishments seen in Nasreddin Hodja's anecdotes were being conveyed based on the relationship of humor, irony, black humor and laughter, the economic, cultural, political and social deformities of the period lived in have been criticized. Thus, the aim is to raise awareness of individuals and enable them to find the right way in terms of governing-governed, by questioning the reasons for the repeated mistakes and the disrupted order. The purpose of this study is to classify the crimes and penalties in the anecdotes of Nasreddin Hodja. In this study, qualitative research method and hermeneutics method are used and also it is also analysed from Nasreddin Hodja anecdotes in various sources. Two basic types of crimes were identified in the anecdotes of Nasreddin Hodja; crimes with social context (theft/extortion, damaging property, perjury, slander, etc.), and crimes against the state (misconduct, bribery, embezzlement, cruelty towards public, etc.). Criminal sanctions like tattooing, riding on donkey, ridiculing, condemnation, insulting, laughing, etc. were applied against these crimes. As a result of the investigations on the anecdotes of Nasreddin Hodja, it is seen that written and oral laws were similar. In the texts, legal awareness was raised by punishing evil types who violated ethical codes and the integrity of society and did perjury.
SUÇ VE CEZA KAVRAMLARI BAĞLAMINDA NASREDDİN HOCA FIKRALARININ TAHLİLİ
Keywords: Nasreddin Hodja; anecdote; humor; crime; punishment